SnO2 Nanostructure as Pollutant Gas Sensors: Synthesis, Sensing Performances, and Mechanism - Brian Yuliarto; Gilang Gumilar; Ni Luh Wulan Septiani (Advances in Materials Science and Engineering)
A significant amount of pollutants is produced from factories and motor vehicles in the form of gas. Their negative impact on the environment is well known; therefore detection with effective gas sensors is important as part of pollution prevention efforts. Gas sensors use a metal oxide semiconductor, specifically SnO2 nanostructures. This semiconductor is interesting and worthy of further investigation because of its many uses, for example, as lithium battery electrode, energy storage, catalyst, and transistor, and has potential as a gas sensor. In addition, there has to be a discussion of the use of SnO2 as a pollutant gas sensor especially for waste products such as CO, CO2, SO2, and NOx. In this paper, the development of the fabrication of SnO2 nanostructures synthesis will be described as it relates to the performances as pollutant gas sensors. In addition, the functionalization of SnO2 as a gas sensor is extensively discussed with respect to the theory of gas adsorption, the surface features of SnO2, the band gap theory, and electron transfer.